Why do some respond and develop more from coaching than others? A systematic review of coachability and its constituent components - MacGabhann, S.; Newman, P.; Witchalls, J.; Dowse, R.; Waddington, G.; Cobley, S. (Sports Medicine, 2025)
Background: As an inter-individual psychological and behavioural construct, coachability is hypothesised to be a fundamental determinant of learning and performance enhancement within sport, business and education domains. Despite its perceived importance, consensus on a precise definition and its exact dimensional components has yet to be established. Objectives: This systematic review aimed to: (1) establish consensus on a common definition and (2) identify consistent constituent component constructs of coachability evident in the literature. Methods: Using systematic search and screening methods, 53 articles (41 studies; 12 grey literature) from sources spanning 5 decades were identified. Results: Findings revealed variable definitions of coachability that evolved with respective theoretical and investigatory paradigm shifts. Nonetheless, throughout, coachability was consistently considered a multi-component construct. Literature supported the existence of potentially six inter-connected component dimensions: Attentiveness to information; Willingness to learn; Persistence in overcoming setbacks; Feedback seeking; Feedback receptivity; and Feedback implementation. For each component, evidence illustrating psychological and behavioural features resonating with higher and lower component presence was identified. Identified components were also validated through independent interviews with sport coaches. Collectively, findings established a synthesised consensus definition aligned with identified component dimensions, reflecting: an individual`s willingness and ability to seek, receive and act upon constructive feedback to persistently foster self-development and enhance performance in a given domain. Conclusions: Given the limited assessments, methodologies and instruments available, research is recommended to refine and validate assessment instruments, verify constituent components identified, confirm relationships between coachability and developmental outcomes, and identify coachability optimisation strategies to benefit personal development within domain contexts.